Translation and validation of the Uterine Fibroid Symptom and Quality of Life (UFS-QOL) questionnaire for the Brazilian Portuguese language - Brito, Luiz Gustavo Oliveira (2017)
CONTEXT AND OBJECTIVE: Uterine fibroids (UF), also known as leiomyomas, are the most prevalent gynecological tumors. The Uterine Fibroid Symptoms and Quality of Life (UFS-QOL) is the only specific questionnaire that assesses symptom intensity and quality-of-life issues for women with symptomatic UF; however, it only exists in the English language. Thus, we aimed to translate and culturally validate the UFS-QOL questionnaire for the Brazilian Portuguese language. DESIGN AND SETTING: Cross-sectional study, Department of Gynecology and Obstetrics, FMRP-USP. METHODS: 113 patients with UF (case group) and 55 patients without UF (control group) were interviewed using the UFS-QOL questionnaire after translation and cultural adaptation. The Short Form-36 questionnaire was used as a control. Demographic and psychometric variables were analyzed. RESULTS: Women with UF presented higher mean age, body mass index, weight, parity and comorbidities than the control group (P < 0.05). The most prevalent complaints were abnormal uterine bleeding (93.8%), pelvic pain (36.3%) and extrinsic compression (10.6%) and these presented adequate construct validity regarding UFS-QOL severity (P < 0.05). The UFS-QOL questionnaire presented good internal consistency regarding symptom severity and quality-of-life-related domains (intraclass correlation coefficient, ICC = 0.82/0.88). Structural validity presented correlation coefficients ranging from 0.59 to 0.91. Test-retest comparison did not show differences among the UFS-QOL subscales. After treatment, women with UF presented improvements on all subscales. CONCLUSION: The UFS-QOL questionnaire presented adequate translation to the Brazilian Portuguese language, with good internal consistency, discriminant validity, construct validity, structural validity and responsiveness, along with adequate test-retest results.